Pengaruh Program Dana Desa Terhadap Perekonomian Masyarakat, Perluasan Lapangan Kerja dan Peluang Usaha Masyarakat Desa (Studi Deskriptif Korelasi pada 10 Desa di Kabupaten Purwakarta) - Eti Jumiati; Duki Adam (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
This study aims to see the effect of the village fund program on the community's economy, expansion of employment and business opportunities for rural communities in Purwakarta Regency. The research method used was Multivariate analysis or MANOVA. The function of MANOVA is to partially determine the effect of the village fund economy program (X) the community economy variable (Y1), on the expansion of employment (Y2) and business opportunities (Y3). And to see the effect simultaneously between the village fund program variables (X) on the community economy (Y1), expansion of employment (Y2) and business opportunities (Y3). The population in this study were 10 villages in Purwakarta Regency, each of which consisted of 10 respondents. The sampling technique used a stratified random sampling technique, taking random samples from each village. The results of the study are as follows: 1) based on a test between the influence or influence of individual variables, that the village fund program variables each affect economic growth, employment expansion and business opportunities. Because all variables have a significance value> than 0.05; 2) based on these tests it is stated that together there is an effect of the village fund program on economic growth, expansion of employment and business opportunities, because the value of F is calculated > from F table.